The Stability of Money Demand in South Africa - Msomi, Simiso; Gumede, Sanele (Acta Universitatis Danubius. Œconomica, 2024)
The stability of money demand is central to South Africa’s monetary policy. Furthermore, it has implications for the work of the SARB, which is the monetary authority of South Africa. Since the year 2000, the SARB has been hawkish in its behaviour, which raises questions about the stability of money demand. This is because, for an inflation-targeting economy that provides information to the public to stabilise the market, its money demand should be stable, thereby making the behaviour of the central bank more stable. However, the SARB's behaviour does not seem to portray the demand for money in South Africa as stable. Hence, this study assesses the demand for money in order to comprehend its behaviour. The study uses the CUSUM test to test for the stability of money demand. And it is found that before the year 2015, money demand was stable. Hence, the demand for money in South Africa has become unstable over time. The sample data used in the study is from 2003 to 2023.